Mycorrhizae and Rhizobacteria on Precambrian Rocky Gold Mine Tailings: I. Mine-Adapted Symbionts Promote White Spruce Health and Growth - Nadeau, Martin B.; Laur, Joan; Khasa, Damase P. (Frontiers in Plant Science, 2018)
White spruce (Picea glauca (Moench) Voss) is a commercially valuable boreal tree that has been known for its ability to colonize deglaciated rock tailings. Over the last decade, there has been an increasing interest in using this species for the revegetation and successful restoration of abandoned mine spoils. Herein, we conducted a glasshouse experiment to screen mycorrhizal fungi and rhizobacteria capable of improving the health and growth of white spruce seedlings growing directly on waste rocks or fine tailings from the Sigma-Lamaque gold mine located in the Canadian Abitibi region. After 32 weeks, measurements of health, growth and mycorrhizal colonization variables of seedlings were performed. Overall, symbionts isolated from roots of healthy white spruce seedlings growing on the mining site, especially Cadophora finlandia Cad. fin. MBN0213 Genbank #KC840625 and Pseudomonas putida MBN0213 GenBank #AY391278, were more efficient in enhancing seedling health and growth than allochthonous species and constitute promising microbial symbionts. In general, mycorrhizae promoted plant health and belowground development, while rhizobacteria enhanced aboveground plant biomass. The observed beneficial effects were substrate-, strain-, and/or strains combination- specific. Therefore, preliminary experiments in control conditions such as the one described here can be part of an efficient and integrated strategy to select ecologically well adapted symbiotic microorganisms, critical for the success of a long-term revegetation program.